2020
DOI: 10.21608/ejchem.2020.31739.2674
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Cytotoxic Activity of Selected Organs of Sambucus nigra L. via Enzyme Assay and Molecular Docking Study

Abstract: The purpose of this study is to shed light on the phenolics content and the presence of different classes of constituents in the flowers, leaves, and stems of Sambucus nigra L. cultivated in Egypt along with screening out their cytotoxic activity. Colorimetric investigation revealed that all tested samples were rich in phenolics. HPLC qualitative analysis revealed the presence of different phenolics including chlorogenic acid and rutin that were isolated and identified using 1 H and 13 C NMR. The ethanolic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…They could decrease the viability of the tested cell lines via the synergistic effects of (poly)phenolic compounds, and the molecular docking study indicated that chlorogenic acid and rutin had the ability to interact with key amino acids in the Bcl-2 binding site. 58 In T24 bladder carcinoma cells and MRC-5 human normal fibroblast cells, the cytotoxic activity of elderberry flower extracts could only be observable in T24 cells but not in MRC-5 cells, suggesting that the elderberry flower extracts are toxic to cancer cells but safe to normal cells, and flavonoids identified in the extract were possibly responsible for the cytotoxic activity. 59 Moreover, micellar solutions of pluronic F127 could enhance the cytotoxic activity.…”
Section: ■ Health Functions Of Elderberrymentioning
confidence: 91%
See 1 more Smart Citation
“…They could decrease the viability of the tested cell lines via the synergistic effects of (poly)phenolic compounds, and the molecular docking study indicated that chlorogenic acid and rutin had the ability to interact with key amino acids in the Bcl-2 binding site. 58 In T24 bladder carcinoma cells and MRC-5 human normal fibroblast cells, the cytotoxic activity of elderberry flower extracts could only be observable in T24 cells but not in MRC-5 cells, suggesting that the elderberry flower extracts are toxic to cancer cells but safe to normal cells, and flavonoids identified in the extract were possibly responsible for the cytotoxic activity. 59 Moreover, micellar solutions of pluronic F127 could enhance the cytotoxic activity.…”
Section: ■ Health Functions Of Elderberrymentioning
confidence: 91%
“…The cytotoxic activity of the ethanolic extracts of the flowers, leaves, and stems of elderberry was also tested in human hepatocellular carcinoma, lung adenocarcinoma, and colon carcinoma cell lines, and it was found that all of the extracts had cytotoxic activities. They could decrease the viability of the tested cell lines via the synergistic effects of (poly)­phenolic compounds, and the molecular docking study indicated that chlorogenic acid and rutin had the ability to interact with key amino acids in the Bcl-2 binding site . In T24 bladder carcinoma cells and MRC-5 human normal fibroblast cells, the cytotoxic activity of elderberry flower extracts could only be observable in T24 cells but not in MRC-5 cells, suggesting that the elderberry flower extracts are toxic to cancer cells but safe to normal cells, and flavonoids identified in the extract were possibly responsible for the cytotoxic activity .…”
Section: Health Functions Of Elderberrymentioning
confidence: 99%